The development of an entrepreneurial business framework in Gauteng province - Livhuani M. Nedzingahe; Zeleke Worku; Mammo Muchie (The Southern African Journal of Entrepreneurship and Small Business Management, 2025)
Background: Entrepreneurs in Gauteng, South Africa’s economic hub, face growing pressure to integrate sustainability into their business models. As responsible operations become essential, the need for supportive frameworks has intensified. Developing a robust framework for sustainable entrepreneurial businesses in Gauteng province can maximise business opportunities and sustainable operations.